KELAYAKAN FINANSIAL DAN STRATEGI PEMASARAN USAHATANI KACANG HIJAU DI DESA DUALASI RAIULUN KABUPATEN BELU - Rosina Melan Tonael; Charles Kapioru; Paulus Un (Journal Education and Government Wiyata, 2026)
Mung bean farming has economic potential for rural communities; however, its sustainability depends on profitability and the implementation of effective marketing strategies. This study aimed to analyze the financial feasibility and marketing strategies of mung bean farming in Dualasi Raiulun Village, Lasiolat District, Belu Regency. The study employed a survey method with quantitative and qualitative descriptive approaches. A total of 51 farmers were selected as respondents based on the research criteria. Financial feasibility was analyzed using production costs, revenue, net income, Revenue Cost Ratio (R/C Ratio), and Break Even Point (BEP), while marketing strategies were analyzed using the 4P marketing mix consisting of product, price, place, and promotion. The results showed that the average production cost was IDR 1,343,137.25, average revenue was IDR 7,701,373, and net income reached IDR 6,358,236 per farmer per growing season. The R/C Ratio of 5.7 indicated that mung bean farming was financially feasible. The production BEP was 82.04 kg, while the price BEP was IDR 6,329.42/kg, both of which were below the actual average production of 424 kg and the average selling price of IDR 16,411.76/kg. The marketing strategy incorporated product, price, place, and promotion elements; however, marketing practices remained dominated by traditional channels through local markets, intermediary traders, personal networks, and word-of-mouth promotion. Strengthening farmer institutions, diversifying marketing channels, improving product quality, and adopting digital marketing are necessary to enhance farmers' bargaining power and income sustainability.